GAMBARAN TINGKAT PENGETAHUAN PASANGAN USIA SUBUR TENTANG PENGGUNAAN ALAT KONTRASEPSI IUD - Ardanti, Ni Komang Junia; Dewi, Ni Luh Made Asri (Coping: Community of Publishing in Nursing, 2023)
Family Planning Program is an effort to create a quality family through promotion, protection and assistance in realizing reproductive rights as well as providing the necessary services, arrangements, and support. Acceptors of the Intra Uterine Device (IUD) still have misconceptions about the use of IUDs, which influences the use of IUD contraceptives. From several studies it was found that education can influence a person, including the acceptor's behavior in choosing a contraceptive method. The aim of this study was to determine the level of knowledge of couples of childbearing age regarding the use of IUD contraception. This type of research is quantitative with a descriptive analytical research design. The research location is UPTD Puskesmas I North Denpasar. The sample in this study was 176 couples of childbearing age, who were selected using a non-probability technique: purposive sampling. The research instrument used was a questionnaire with 10 knowledge questions about the use of IUD contraception. Data were analyzed with univariate tests. The research results showed data on the characteristics of respondents in the 20-35 years age range as many as 103 respondents (58,5%), SMA/SMK education was 112 respondents (63,6%), and private employment was 77 respondents (43,8%). The level of PUS knowledge in the use of IUD contraception was mostly in the good category with 122 respondents (69,3%).